2015
DOI: 10.1002/oby.21312
|View full text |Cite
|
Sign up to set email alerts
|

Protein source in a high‐protein diet modulates reductions in insulin resistance and hepatic steatosis in fa/fa Zucker rats

Abstract: Objective: High-protein diets are being promoted to reduce insulin resistance and hepatic steatosis in metabolic syndrome. Therefore, the effect of protein source in high-protein diets on reducing insulin resistance and hepatic steatosis was examined. Methods: Fa/fa Zucker rats were provided normal-protein (15% of energy) casein, high-protein (35% of energy) casein, high-protein soy, or high-protein mixed diets with animal and plant proteins. Results: The high-protein mixed diet reduced area under the curve fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 39 publications
4
22
1
1
Order By: Relevance
“…This is in line with a cross-sectional analysis showing an increased risk of overweight and obesity in women consuming a greater proportion of energy from protein (Murtaugh et al 2007). However, as previously reported in these rats, the HP diets resulted in higher lean mass (Wojcik et al 2016), consistent with studies indicating that one of the benefits of HP diets is their effect on sparing fat free mass during weight loss , Claessens et al 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with a cross-sectional analysis showing an increased risk of overweight and obesity in women consuming a greater proportion of energy from protein (Murtaugh et al 2007). However, as previously reported in these rats, the HP diets resulted in higher lean mass (Wojcik et al 2016), consistent with studies indicating that one of the benefits of HP diets is their effect on sparing fat free mass during weight loss , Claessens et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…We have previously reported that an HP diet composed of mixed proteins (compared to single protein sources of casein or soy protein) was more effective in reducing insulin resistance and hepatic steatosis independent of weight loss in the obese fa/fa Zucker rat (Wojcik et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…There was no difference in fasting plasma glucose between lean or obese animals or between dietary treatments. These findings are supported by studies in humans [55,56], which have demonstrated that long-term high-protein diets have little effect on fasting plasma glucose levels, as well as in animal studies [57]. Although we did not collect postprandial data in this study, Bernard et al [58] have shown that an amino acid mixture (high in the BCAA leucine) can improve glucose tolerance and decrease insulin resistance in obese, Zucker rats in an acute setting.…”
Section: Discussionsupporting
confidence: 55%
“…However, no significant differences were found for systolic or diastolic blood pressure in other meta-analyses comparing HP diets to LP [7,39]. It is thought that HP consumption is responsible for higher intake of sodium hence subsequent hypertension but there is no valid data to support this claim [49,50]. In the Omni Heart study a HP diet (25% energy as HP, 48% as carbohydrate) compared with a high carbohydrate diet (15% energy as protein, 58%…”
Section: Hp Diets and Healthmentioning
confidence: 99%